Anna de Juan Capdevila. Issue 7 (November 2015) - Downey, Gerry
In this interview, we have departed a little from profiles of mainstream NIR researchers and hear from Dr Anna de Juan Capdevila. Anna will be known to many of our readers as one of the leading chemometricians involved in developing new ways to process and interpret hyperspectral images. I hope you find her profile as interesting as I did.—Ed.